'Too Unsavoury for Our Fastidious Tastes': Unmarried Motherhood in South Africa's Mother City, Cape Town, 1910–1948. Issue 2 (3rd April 2021) - Richardson, Laura
ABSTRACT: Focusing on the establishment of maternity care services predominantly for young, working-class white and coloured unmarried mothers, this article examines social and institutional responses to and changing conceptions of single motherhood and illegitimacy in early to mid-twentieth-century Cape Town, then one of the country's largest and most well-established urban centres. It suggests that despite growing organisational support for the plight of the unmarried mother, such women continued to be seen as deviant and were treated in a manner that affirmed this status, although it is possible to track significant shifts in the way in which social workers and the government understood single motherhood between 1910 and 1950. It also argues that in Cape Town specifically, competing racial and religious concerns modulated the language used to describe unmarried motherhood, determining what kinds of services were available, where and for whom.